Violation of Politeness Principles in Wkwk Project Talk Show and Their Relevance to Students’ Listening Competence - Jelitasani, Ardina Rosanatan; Sulistyono, Yunus (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe violations of the politeness principles found in the Wkwk Project talk show and analyze their relevance to listening competence in language learning. Methodology: A qualitative descriptive approach was employed to analyze episodes of the “Bocah Bocah Kosong” program on the Wkwk Project (Genflix YouTube channel). Data were collected through listening and recording techniques, focusing on the interactions between the three hosts Meyden, Vior, and Chateez and various guest stars. The analysis identified deviations from Leech’s politeness maxims. Results: Five types of politeness violations were found: violations of the maxims of wisdom, generosity, praise, humility, and sympathy. The hosts often used sarcastic and inappropriate language, including examples where guest stars such as Maia Estianty were addressed disrespectfully. These patterns of speech reflect significant violations of language politeness principles. Applications/Originality/Value: This study reveals that frequent violations of politeness principles in popular media content such as talk shows may negatively affect students’ listening competence. Exposure to impolite or entertaining but irrelevant language may hinder learners’ ability to distinguish essential information and reduce the effectiveness of classroom listening activities. These findings underline the importance of selecting appropriate media for educational purposes.